(untitled) (Analysis in Theory and Applications, 2012)
In this article we introduce the difference sequence spaces W_0[ f, Δ m], W_1[ f ,Δ m],W_∞[ f ,Δ m] and S[f,Δ m], defined by a modulus function f. We obtain a relation between W_1[ f ,Δ m]l_∞[ f ,Δ m] and S[ f ,Δ m]l_∞[ f ,Δ m] and prove some inclusion results.